Enhancing Intrinsic Motivation in Academic Settings: The Role of Self-Regulation Skills Interventions - Sarami, Paria; Hojjati, Marziyeh (KMAN Counseling & Psychology Nexus, 2023)
This study aimed to investigate the effects of self-regulation skills (SRS) training on the intrinsic motivation of secondary school students. The primary objective was to determine whether an intervention focused on enhancing SRS skills could lead to significant improvements in students’ intrinsic motivation over time. The study utilized a quasi-experimental design with a control group, involving 30 students (15 in the experimental group and 15 in the control group) from a secondary school. The experimental group underwent an 8-week intervention program designed to improve their SRS training, while the control group received no such intervention. Intrinsic motivation was measured at three points: before the intervention (pre-test), immediately after (post-test), and four weeks following the intervention (follow-up), using a validated intrinsic motivation inventory. Descriptive statistics and analysis of variance with repeated measurements indicated significant increases in intrinsic motivation scores from pre-test to post-test and from pre-test to follow-up in the experimental group. The control group, however, showed no significant changes over time. The interaction between time and group was also significant, suggesting that the intervention had a positive effect on enhancing intrinsic motivation among the experimental group participants. The findings suggest that interventions aimed at enhancing self-regulated learning strategies can have a positive impact on secondary school students’ intrinsic motivation. The sustained improvement from post-test to follow-up indicates that the benefits of such interventions are not only immediate but also enduring.